Stability analysis and support scheme optimization design of roadway surrounding rock in shallow coal seam with thin bedrock - Pei, Zhang; Chunyu, Ji; Shuchao, Guo; Jiayao, Fu; Chenghong, Wu (Frontiers in Built Environment, 2025)
This study examines the stability of the surrounding rock in the 3–1 coal mining roadway of Hejiata Coal Mine, focusing on shallow coal seams with thin bedrock through laboratory tests, similar material simulations, and numerical modeling. It first analyzes the mechanical behavior of roof and floor rocks, then proposes an optimized roadway support system based on the analysis results. Results indicate the weathered rock and floor mudstone exhibit unstable characteristics, while the immediate roof composed of medium-grained sandstone and main roof of fine-grained sandstone demonstrate overall instability with localized medium stability. Water immersion tests reveal weathered rock develops initial bedding cracks followed by annular fractures before stabilizing, whereas mudstone experiences continuous argillization leading to progressive surface cracking. The immediate roof shows initial caving at 18 m, with the main roof’s first weighting occurring at 36 m, followed by periodic fractures every 8–16 m. At 78 m advancement, overlying strata collapse in a distinctive arc rock pillar formation. Stress analysis shows that mining induces stress redistribution in surrounding rock, creating localized stress concentration zones and forming an arch-shaped stress relief area in the roof and floor strata. Abutment pressure evolution reveals increasing peak values and influence ranges below 140 m advancement, transitioning to intensified stress concentration upon roof-floor contact beyond this threshold. Deformation monitoring shows progressive increases in roof displacement and floor heave, with maximum values occurring near the goaf center. The optimized support design specifies bolts with 2.1 m length, 20 mm diameter, 0.8 m spacing, and 25 kN pre-tightening force, complemented by anchor cables measuring 5 m in length, 15.24 mm in diameter, spaced at 2.4 m intervals, with 70 kN pre-tightening force and 180 kN anchoring capacity.